자동굴절검사기를 이용한 연령에 따른 객관적 조절력 평가 - 강동완(Dong Wan Kang), 엄영섭(Young Sub Eom), 임재원(Jay Won Rhim), 강수연(Su Yeon Kang), 김효명(Hyo Myung Kim), 송종석(Jong Suk Song) (Daihan angwa haghoi jabji, 2016)
목적: 자동굴절검사기를 이용하여 다양한 연령대에서 객관적 조절력을 평가하고 이를 주관적 조절력 평가 결과와 비교하였다. 또한 백내장 수술 후 인공수정체안에서도 객관적 조절력이 어떠한지 알아보았다. 대상과 방법: 2014년 7월부터 2014년 8월까지 고려대학교 구로병원으로 내원한 수정체안 41명 41안을 10대 이하부터 60대 이상까지 6군의 연령대별로 나누어 자동굴절검사기로 측정된 5 m에서의 원거리 굴절값과 20 cm에서의 근거리 굴절값을 이용하여 객관적 조절력을 측정하였다. 또한 20명 20안에서는 마이너스 렌즈 방법을 이용하여 주관적 조절력을 측정하여 객관적으로 측정된 조절력과 비교하였다. 끝으로 백내장 수술 후 인공수정체안 8명 8안을 대상으로 하여 객관적으로 조절력이 어떠한지를 평가하였다. 결과: 정상인의 조절력 평균은 2.38D, 각 연령별 객관적 조절력은 10대 3.31 ± 0.99D, 20대 3.25 ± 0.34D, 30대 3.78 ± 0.68D, 40대 1.00 ± 0.60D, 50대 0.22 ± 0.23D, 60대 0.00 ± 0.00D로 40대부터 급격한 감소를 보였으며, 객관적 조절력과 주관적 조절력은 유의한 양의 상관관계를 보였다(Pearson correlation coefficient 0.838). 그러나 주관적 조절력에서는 60세 이상의 피검자에서도 약 1D의 위조절력이 남아 있었다. 인공수정체안에서의 객관적 조절력은 평균 0.10 ± 0.23D, 주관적 조절력은 평균 0.59 ± 0.35D로 유의한 차이를 보였다(p=0.015). 결론: 자동굴절검사기를 사용한 객관적인 방법으로 조절력을 측정하는 것은 향후 노안과 관련된 약물이나 치료의 효과를 평가하는데 유용하게 사용될 수 있겠다. Purpose: To evaluate the objective amplitude of accommodation in various age groups using an autorefractometer and to compare the results with subjective assessments on accommodation. Objective accommodative amplitude of artificial lenses in post-operative cataract patients was also measured. Methods: In this study, 41 patients who visited Korea University Guro Hospital from July through August 2014 were categorized into 6 different age groups. Accommodative amplitude was measured using long-distance refraction at 5 m and short-distance refraction at 20 cm. In 20 patients, subjective amplitude of accommodation was measured using the minus lens technique and was compared with the measured objective accommodative amplitude. Accommodative amplitude was also measured in 8 patients who received cataract surgery. Results: The mean accommodative ability in normal people was 2.38 D. The age groups of 10-19, 20-29, 30-39, 40-49, 50-59, and over 60 years showed accommodative amplitudes of 3.31 ± 0.99 D, 3.25 ± 0.34 D, 3.78 ± 0.68 D, 1.00 ± 0.60 D, 0.22 ± 0.23 D, 0.00 ± 0.00 D, respectively. The results showed a rapid decrease in accommodative ability of patients older than 40 years and demonstrated a correlation between objective and subjective amplitude of accommodation (Pearson’s correlation coefficient 0.838). There was a significant difference between objective and subjective accommodative amplitudes in artificial lenses (p = 0.015), with average objective and subjective measures of 0.10 ± 0.23 D and 0.59 ± 0.35 D, respectively. Conclusions: Measuring amplitude of accommodation using an autorefractometer can be useful in assessing results of presbyopia treatment. KCI Citation Count: 2